2021
DOI: 10.3390/jcm10051059
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Vitrectomy with Vancomycin Infusion, Silicone Oil Endotamponade, and General Antibiotic Treatment in Multiple Cases of Endophthalmitis from a Single Day of Intravitreal Injections—Case Series

Abstract: The aim of this study was to report on the anatomical and functional results of surgical management of seven cases of endophthalmitis related to a single day of intravitreal aflibercept injections. Patients with signs of endophthalmitis who underwent aflibercept injections (seven eyes) performed on the same day were retrospectively evaluated. The data of visual acuity and optical coherence tomography (OCT) within nine months of the follow-up and the treatment and results of microbiological cultures are reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…post cataract surgery: 0.05-0.68%; post intravitreal injection: 0.02-0.03%). Acute endophthalmitis usually appears within one to 2 weeks after the primary surgical interventions (the median onset of post-operative endophthalmitis after cataract surgeries: 9 days; post intravitreal injection: 24 h) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…post cataract surgery: 0.05-0.68%; post intravitreal injection: 0.02-0.03%). Acute endophthalmitis usually appears within one to 2 weeks after the primary surgical interventions (the median onset of post-operative endophthalmitis after cataract surgeries: 9 days; post intravitreal injection: 24 h) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable for any ophthalmologist to treat endophthalmitis. Studies have concluded that vitrectomy is effective for the initial treatment of endophthalmitis; early vitrectomy (i.e., within 24 h) might be helpful in achieving a better visual outcome [2,4,46,51], and a primary vitrectomy demonstrated greater visual improvement [2,18,47]. However, the European Vitreo-Retinal Society Endophthalmitis Study showed similar outcomes after treatment with intravitreal antibiotics alone compared with intravitreal antibiotics and vitrectomy within 1 week of presentation [45].…”
Section: Discussionmentioning
confidence: 99%
“…The foundation of the treatment for bacterial endophthalmitis is focal and systemic administration of antibiotics; vitrectomy is performed if the endophthalmitis is severe. Unless the patient receives appropriate treatment early in the disease, it causes irreversible damage to the retina, which results in a high probability of vision loss [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a purulent inflammation of the intraocular fluids comprising the vitreous and the aqueous humor. Although the etiology of this condition can be both endogenous and exogenous, it is mostly secondary to intraocular surgeries, injections or penetrating ocular trauma [16]. The incidence of endophthalmitis after cataract surgery is low with reports of 0.076% [17], 0.02% [18] and 0.048% [19].…”
Section: Increase Of Multidrug-resistant Bacteria and Fungi Causing Endophthalmitismentioning
confidence: 99%